Mobile UiTM qualification checking system using Analytical Hierarchy Process (AHP) technique / Zawawi Ismail@ Abdul Wahab and Nur Fadhlina Ab Rahman - Ismail@ Abdul Wahab, Zawawi; Ab Rahman, Nur Fadhlina (2016)
UiTM has developed a web-based system called Selangkah ke UiTM for candidates especially secondary school leavers who have undergone SPM examination to check qualified programmes offered in the university. From an initial study conducted, it is found that the sytem has not been built to meet some preferences of the candidates such as duration and field of study. In addition, the candidates need to get persistent connection to the Internet in order to log on to the system. Therefore, a mobile application using Analytic Hierarchical Process (AHP) or called m-Selangkah is proposed to help the candidates in selecting their preferred programmes based on the SPM result. m-Selangkah allows the user to use it anywhere anytime once it is downloaded to the mobile phone. The application is integrated with multi-criteria decision making (MCDM) AHP method will allow the users to choose their qualified programmes based on their preferences. It is developed based on phases in the RAD model which are preliminary study, system analysis, system design, system development, system testing and evaluation, and finally documentation. The functionality of m-Selangkah application has been tested using real data by focusing the scope to programmes offered by Terengganu campus. The usability of this application is evaluated by conducting a set of questionnaires to the random respondents. The results showed that most of the respondents agreed the proposed application has the potential and moderately useful.